The Bonhoeffer legacy : Australasian journal of Bonhoeffer studies - Lovat, Terence; Clements, Keith (Bonhoeffer Legacy : Australasian Journal of Bonhoeffer Studies, 2014)
""Research Articles:Resurrection and Reality in the Theology of Dietrich BonhoefferChristopher RJ Holmes Bridging the Gap: Dietrich Bonhoeffer's Early Theology and its Influence on DiscipleshipJoseph McGarry Binding Sovereignties: Dietrich Bonhoeffer and the VirtuesDallas Gingles Hermann Sasse and Dietrich Bonhoeffer: Churchmen on the BrinkMaurice Schild 'Lord of the (Warming) World': Bonhoeffer's Eco-theological Ethic and the Gandhi FactorDianne Rayson & Terence Lovat Other Article:The Bonhoeffer Society as MentorKeith ClementsBook Reviews:Derek McDougallMaurice Schild Gordon Watson""